Al-Mu‘tazilah wa Musāhamātihim fī al-Fikr al-Islāmī - Engku Alawi, Engku Ahmad Zaki (Jurnal Usuluddin, 2003)
This article attempts to view the significance of al-Mu’tazilah in the development of Islamic theology. They played a vital role in introducing and developing the methodology of Islamic theology and their impact was so great especially information of Islamic epistemology in the field of usul al-Din. It highlights the five important principles of Mu’tazilah and reviews the differences between them and al-Asya’irah in understanding the al-Qada’ and al-Qadar issue according to al-Quran and al-Sunnah guidelines.